Electroproduction of lightest nucleon resonances up to Q*2=12 GeV*2 in quark models at light front; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 138 : High Energy Physics Problems Relativistic Nuclear Physics and Quantum Chromodynamics (Baldin ISHEPP XXIII) - Obukhovsky I. T. Igor Timofeevich; Faessler A.; Gutsche T. Thomas; Fedorov D. K. Dmitry Konstantinovich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2017, 2017)
Title screen